Counter- and co-directed swirling-type waves due to orbital excitations of a square-base tank - Lagodzinskyi, O.E.; Timokha, A.N. (Доповіді НАН України, 2021)
The analytic technique and numerical experiments are employed to show that the orbital elliptic translational ex citations
of a square-base container can, depending on the ratio of the semiaxes of the elliptic orbit, lead, when the
forcing frequency is close to the lowest natural sloshing frequency, to both the counter- and co-directed (relative
to the orbital forcing direction) stable swirling-type steady-state resonant waves. For a non-zero damping in the
hydrodynamic wavy system, the passage to circular orbits makes the stable counter-directed swirling impossible. Застосовується аналітична техніка та чисельні експерименти для того, аби показати, що орбітальні еліптичні поступальні збурення баку квадратного перерізу можуть призвести в залежності від співвідношен ня напіввісей еліптичної орбіти до як проти- так і співнаправленої (відносно напрямку збурення баку) стійкої усталеної кругової хвилі. Частоти збурення близькі до першої власної частоти коливання рідини.
Для ненульового демпфування в гідродинамічній системі перехід до кругових орбіт робить неможливими
протинаправлені кругові хвилі.